Imlek Sebagai Permohonan Dan Syukur - . Harsono (Arete, 2017)
The central point of Imlek’s celebration is ritual. The ritual of Imlek lasts for 21 days. It begins with a prayer to The God of the Kitchen and is ended by Lampion Festival. The main purposes of all rituals in Imlek are to achieve prosperity, serenity, and happiness. For Langer, ritual is a kind of symbol. Ritual is an actualization of human expression because the relation between human and symbol is essential and integral. This expression forms a certain pattern. Then, that pattern forms a role making that makes each person who wants join it must follow that pattern. Later, this pattern forms a ritual. In this research, the ritual is an expression of gratitude. People who celebrate Imlek offer thanksgiving to God (Thian). This gratitude also contains of hope, namely the blessing of Thian in the coming year. An important part of this act is a lively celebration which is performed in such away that people can experience and feel the gratitute.